2019
DOI: 10.1016/j.trc.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social influence and social interactions on the adoption of a new technology: The use of bike sharing in a student population

Abstract: The present study investigates how social influence and social interactions can affect the adoption of new technologies, using stated preference (SP) survey data combined with an "accelerated reality" experience of social interaction among the respondents. Specifically, the intention to use a pro-environmental transport mode (the bike sharing) during a public transport strike within a cohort of students has been analysed. Previous studies have modelled social influence effects using SP data by providing a hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…In developing nations like India, people generally live in joint families and depend on each other in numerous socio-economic contexts (Owens, 1971;Ray et al, 2019). Thus, the adoption of digital health consultation services in this kind of situation will not only become noticeable to their close friends and family members but also their view can inspire them to use the same (Ray et al, 2019;Manca et al, 2019). Hence, it is imperative to examine the relationship between SI and the BI of users towards the adoption of digital health consultation.…”
Section: Theories Of Technology Acceptancementioning
confidence: 99%
“…In developing nations like India, people generally live in joint families and depend on each other in numerous socio-economic contexts (Owens, 1971;Ray et al, 2019). Thus, the adoption of digital health consultation services in this kind of situation will not only become noticeable to their close friends and family members but also their view can inspire them to use the same (Ray et al, 2019;Manca et al, 2019). Hence, it is imperative to examine the relationship between SI and the BI of users towards the adoption of digital health consultation.…”
Section: Theories Of Technology Acceptancementioning
confidence: 99%
“…Yao et al further demonstrated that the credit supervision mechanism was more appealing to attract cyclists to ride shared bikes when a negative credit is introduced [30]. The social interaction influences cyclists' bikesharing choice by inducing family members or close friends to make the same choices [31]. The service quality is a relatively comprehensive factor and is proved to have a positively significant effect on the intention to ride shared bikes [32].…”
Section: Influential Factorsmentioning
confidence: 99%
“…We have associated three constructs as social influence, citizens' empowerment, and facilitating conditions with digital society affinity. The social influence is related to the citizens that get influenced by other citizens in society and develop a negative or positive impact to use IoT services, it generally focuses on the citizens in a society affected by their peers' behaviour (Manca et al, 2019). It is considered to be a powerful construct in many types of research regarding smart government services (Alshehri et al, 2012), which highlights the positive social interaction influence on citizens' intentions to use smart government services.…”
Section: Digital Society Affinity To Intensify the Perceived Valuementioning
confidence: 99%
“…In quest of the research objectives, we have conducted a study on the conceptual phenomena of Unified Theory of Acceptance and Use of Technology (UTAUT), Technology Acceptance Model (TAM), and Theory of Planned Behaviour (TPB). The success of IoT service orchestration in the public sector requires the integration of citizens' trust (Bahutair et al, 2019;Nelson & Gorichanaz, 2019) and digital social affinity (Bigné et al, 2007;Manca et al, 2019). We have developed a conceptual model IoT-PVM after formulating the research hypotheses and it was subsequently tested through PLS-SEM.…”
Section: Introductionmentioning
confidence: 99%